A clinical study of the relationship between Triglyceride/Glucose index (TyG index) and Glycated hemoglobin(HbA1c )in patients with Diabetes Mellitus Type 2 - ناصر هديل; أريج بوبو; فيصل رضوان (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Diabetes Mellitus is a global health issue due to the huge number of patients worldwide and its devastating complications. ADA recommended achieving a good glycemic control to avoid that by reaching HbA1c ˂ 7%. Insulin resistance is one of the pathophysiology of T2DM many ways have been used to evaluate it including HOMA-IR & HEC and lately TYG index. Materials and Methods: a total of 83 patients T2DM were included in this prospective cross sectional study and divided into 3 groups according to their HbA1c, a group with good control diabetes HbA1c˂7%, a group of intermediate control HbA1c 7-9% ,a group of bad control HbA1c˃ 9%. Anthropometric and biochemical parameters were measured, TYG index was calculated using formula TYG index = ln [fasting glucose(mg/dl) ͯ fasting triglyceride(mg/dl)] / 2 Results: fasting blood glucose and fasting triglyceride and HDL were higher in patients with HbA1c˃7%, TYG index correlates with HbA1c also TYG-BMI & TYG-WC, the receiver area under curve analyze ROC showed TYG index had a maximum area under curve of 0.852 with a cut-off value 4.9 for identifying glycemic control in T2DM sensitivity 85.5% and specificity 63.2%. Conclusion: TYG index is a useful tool for assessing glycemic control in T2DM and positively correlate with HbA1c, it can be used as a simple, available, and inexpensive alternative to asses glycemic control in T2DM.